An Analysis of Factors Affecting Work Productivity of Employee at Sukaraja Sub-District Office of Seluma Regency of Bengkulu Province - Egy Valistin; Ida Ayu Made Er Meytha Gayatri; Andriyani Prawitasari (Penerbit Jurnal Indonesia, 2021)
The purpose of this study is to determine factors such as motivation and work discipline that affect work productivity of employees at Sukaraja Sub-district Head Office of Seluma Regency. The sample in this study was 29 employees at Sukaraja Sub-district Head Office of Seluma Regency. The data Collection technique used is a questionnaire and the analytical method used is multiple linear regression, determination test and hypothesis testing. The results of the regression equation are Y = 10,107 + 0,417X1 + 0,361X2+ which means that motivation and work discipline have a positive influence on employee productivity at Sukaraja Sub-district Head Office of Seluma Regency. This illustrates that if the motivation and work discipline variables increase, the employee's work productivity will also increase. The result of the determination test is 0.567 or (56.7%). This shows that motivation and work discipline affect work productivity of employees at Sukaraja Sub-district Head Office of Seluma Regency by 56.7%, while the rest (100 - 56.7% = 43.3%) are explained or influenced by other variables not examined. Motivation and work discipline together have an influence on the work productivity of the employees at Sukaraja Sub-district Head Office of Seluma Regency, with a significant value of 0.000, less than 0.05. Motivation has a positive and significant effect on employee work productivity, because the significant value of 0.015 is smaller than 0.05. Work discipline has a positive and significant effect on employee work productivity, with a significant value of 0.028, which is smaller than 0.05.